Netter's atlas of human anatomy for CPT coding - Kirschner, Celeste G.; Netter, Frank H. (Frank Henry), 1906-1991.; American Medical Association (Chicago, Ill. : American Medical Association, 2009)
'This book incorporates illustrations drawn by Frank H. Netter to teach the complete anatomy of the human body in the context of CPT coding. This edition includes new and revised imaging and clinical images'--Provided by publisher.
Head and neck -- Back and spinal cord -- Thorax -- Abdomen -- Pelvis and perineum -- Upper limb -- Lower limb.
Keywords: Anatomy -- Atlases; Anatomy -- Terminology -- English